A rare case report of a mixed persistent proatlantal intersegmental artery. (March 2019) - Ma, Gao-Ting; Zhang, Zi-Xian; Deng, Yi-Ming; Gao, Feng; Miao, Zhong-Rong; Sun, Xuan
Highlights: Persistent proatlantal intersegmental artery. Mixed type. Internal carotid artery stenting. Abstract: Adults with persistent proatlantal intersegmental artery (PPIA) are rarely seen. We present a case of a special type of PPIA that was in a 57-year-old man who presented with dizziness and episodic vertigo of 9 months duration. The diagnosis relied on computed tomography angiography and digital subtraction angiography, by which a left internal carotid artery stenosis and an ipsilateral PPIA originating from the external carotid artery (ECA) was found. This special type of PPIA can be described as a ''mixed PPIA'' that originated as Type II from the ECA and coursed as Type I. The patient underwent carotid artery stenting and had no relapse during 3 months follow-up. In addition, the literatures on PPIA were reviewed.